DMAP-Catalyzed Regel-Type Direct C-2 (Hetero)Aroylation of Oxazoles and Thiazoles Derivatives with Acid Chlorides - Lassalas, Pierrik; Marsais, Francis; Hoarau, Christophe (Synlett, 2013)
A Regel-type transition-metal-free direct C-2 aroylation of (benzo)oxazoles, (benzo)thiazoles and 1,3,4-oxadiazoles with acid chlorides catalyzed by N,N-dimethyl-4-aminopyridine (DMAP) is described. This methodology is effective with several aroyl and heteroaroyl chlorides affording the corresponding 2-ketoazoles in moderate to excellent yields.
Keywords: acylation; azoles; C–H functionalization; heterocycles; metal-free; regioselectivity